2021
DOI: 10.3390/ijms22041895
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Argon Plasma Regulates Skin Moisturizing and Melanogenesis-Regulating Markers through Yes-Associated Protein

Abstract: Extensive water loss and melanin hyperproduction can cause various skin disorders. Low-temperature argon plasma (LTAP) has shown the possibility of being used for the treatment of various skin diseases, such as atopic dermatitis and skin cancer. However, the role of LTAP in regulating skin moisturizing and melanogenesis has not been investigated. In this study, we aimed to determine the effect of LTAP on yes-associated protein (YAP), a major transcriptional coactivator in the Hippo signaling pathway that is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…HA is a key contributor to skin moisture retention and thus reduces skin wrinkling [ 20 ]. Keratinocytes were used to analyze HA synthesis related to skin moisturizing ability [ 46 ]. To determine if CSFAb affects HA levels, we examined the effect of CSFAb on HA synthesis in HaCaT cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HA is a key contributor to skin moisture retention and thus reduces skin wrinkling [ 20 ]. Keratinocytes were used to analyze HA synthesis related to skin moisturizing ability [ 46 ]. To determine if CSFAb affects HA levels, we examined the effect of CSFAb on HA synthesis in HaCaT cells.…”
Section: Resultsmentioning
confidence: 99%
“…HA can bind water molecules, which is important for retaining moisture and maintaining skin elasticity [ 20 ]. It has been reported that low HA levels in skin are associated with water loss and wrinkle formation [ 46 ], and that topical application of HA reduced the wrinkling of aged skin [ 47 ]. HAS synthesizes HA and has three isoforms, viz., HAS-1, -2, and -3, in mammals [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the HA content of the skin decreases gradually as skin aging progresses [ 12 ]. A decline in HA in the skin leads to dehydration, which can cause wrinkles and abnormal skin barrier function [ 52 ]. As shown in Figure 3 , Pp-EE increased the mRNA expression of HAS , which synthesizes HA, and suppressed the mRNA expression of Hyal , which degrades HA.…”
Section: Discussionmentioning
confidence: 99%
“…Skin is the primary defense organ against a harmful external environment. In addition, skin functions as a sensory receptor and regulator of body temperature and moisture content [ 1 , 2 ]. These additional functions of skin contribute to skin homeostasis.…”
Section: Introductionmentioning
confidence: 99%